Emerging Trends and Hot Spots in Sepsis-Associated Encephalopathy Research From 2001 to 2021: A Bibliometric Analysis - Zhang, Yizhe; Chen, Sifan; Tian, Weitian; Zhu, Hui; Li, Weiwei; Dai, Wanbing; Zhang, Xiao; Gu, Xiyao; Su, Diansan (Frontiers in Medicine, 2022)
Study Objectives. To evaluate sepsis-associated encephalopathy (SAE) research and to quantitatively and qualitatively predict research hot spots using bibliometric analysis. Methods. We extracted relevant publications from the Web of Science Core Collection on July 28, 2021. We investigated the retrieved data by bibliometric analysis (e.g. co-cited and cluster analysis, keyword co-occurrence) using the software CiteSpace and VOSviewer, the Online Analysis Platform of Literature Metrology (http://bibliometric.com/) and Bibliometrix to analyse and predict the trends and hot spots in this field. Main Results. We identified 1,582 published articles and reviews on SAE from 2001 to 2021. During this period, the number of manuscripts on SAE increased steadily and peaked in 2021. The USA and China were the leading countries that had critical impact on SAE research. Among all the institutions, the Vanderbilt University and Pittsburgh University held leading positions and became central in the collaboration network. Among all the journals, Critical Care Medicine published the most number of manuscripts in the field of SAE within 20 years. Dal-Pizzol Felipe was the most productive author (61 papers) and received the largest amount of citations (930 citations). Co-citation cluster analysis revealed that the most popular terms on SAE in the manner of cluster labels were critical illness, sepsis-associated encephalopathy, polymicrobial sepsis, posterior reversible encephalopathy syndrome, rat brain, intensive care unit, prior sepsis, molecular hydrogen, inflammation drive, metabolic encephalopathies, delirium pathophysiology and clinical neuroscience. Keyword burst detection indicated that neuroinflammation, blood brain barrier and mitochondria dysfunction were the current research hot spots. Conclusions. Our study revealed that neuroinflammation, blood brain barrier and mitochondria dysfunction had been the research foci of SAE over the past 20 years. These have emerged as basis for transformation from basic research to clinical application in finding effective methods for the prevention and treatment of SAE.